DNA methylation analysis by bisulfite next-generation sequencing for early detection of oral squamous cell carcinoma and high-grade squamous intraepithelial lesion from oral brushing. Issue 8 (October 2015) - Morandi, Luca; Gissi, Davide; Tarsitano, Achille; Asioli, Sofia; Monti, Valentina; Del Corso, Giacomo; Marchetti, Claudio; Montebugnoli, Lucio; Foschini, Maria Pia
Abstract: Purpose: Oral squamous cell carcinoma (OSCC) is commonly preceded by oral potentially malignant lesions (OPML). The aim of the present study was to assess, by bisulfite next-generation sequencing (NGS), the methylation status of a list of candidate genes obtained from oral brushings to early detect OPML and OSCC. Material and methods: Oral brushing specimens from 11 OSCC, 11 high-grade squamous intraepithelial lesions (HG-SIL), 9 low-grade SIL (LG-SIL), 9 oral lichen planus (OLP), and 8 healthy donors were included in this study. We investigated, by means of bisulfite NGS, the promoter of GP1BB, ZAP70, KIF1A, p16[CDKN2A], CDH1, miR137, and miR375. Statistical significance between lesions and a pool of healthy donors were evaluated with the Mann–Whitney U test. Results: ZAP70 was found to be hypermethylated in 100% of OSCC and HG-SIL and in 28.6% of LG-SIL. GP1BB hypomethylation was detected in 90.9% OSCC and HG-SIL and in 37.5% of LG-SIL. MiR137 was hypermethylated in 100% of OLP, 44.4% of OSCC, 40% HG-SIL, and 25% LG-SIL. KIF1A hypermethylation was found to be associated with TP53 mutations ( p  < 0.0001). Conclusion: In the present preliminary cohort of patients, DNA methylation analysis of GP1BB and ZAP70 seems to be a promising noninvasive tool for early detection of OSCC and HG SIL from oral brushing specimens.